Genomic aberrations frequently alter chromatin regulatory genes in chordoma. Issue 7 (9th May 2016) - Wang, Lu; Zehir, Ahmet; Nafa, Khedoudja; Zhou, Nengyi; Berger, Michael F.; Casanova, Jacklyn; Sadowska, Justyna; Lu, Chao; Allis, C. David; Gounder, Mrinal; Chandhanayingyong, Chandhanarat; Ladanyi, Marc; et al.
Abstract : Chordoma is a rare primary bone neoplasm that is resistant to standard chemotherapies. Despite aggressive surgical management, local recurrence and metastasis is not uncommon. To identify the specific genetic aberrations that play key roles in chordoma pathogenesis, we utilized a genome‐wide high‐resolution SNP‐array and next generation sequencing (NGS)‐based molecular profiling platform to study 24 patient samples with typical histopathologic features of chordoma. Matching normal tissues were available for 16 samples. SNP‐array analysis revealed nonrandom copy number losses across the genome, frequently involving 3, 9p, 1p, 14, 10, and 13. In contrast, copy number gain is uncommon in chordomas. Two minimum deleted regions were observed on 3p within a ∼8 Mb segment at 3p21.1–p21.31, which overlaps SETD2, BAP1 and PBRM1 . The minimum deleted region on 9p was mapped to CDKN2A locus at 9p21.3, and homozygous deletion of CDKN2A was detected in 5/22 chordomas (∼23%). NGS‐based molecular profiling demonstrated an extremely low level of mutation rate in chordomas, with an average of 0.5 mutations per sample for the 16 cases with matched normal. When the mutated genes were grouped based on molecular functions, many of the mutation events (∼40%) were found in chromatin regulatory genes. The combined copy number and mutation profiling revealed that SETD2 is the single gene affected most frequently in chordomas, either by deletion or by mutations. Our study demonstrated that chordoma belongs to the C‐class (copy number changes) tumors whose oncogenic signature is non‐random multiple copy number losses across the genome and genomic aberrations frequently alter chromatin regulatory genes. © 2016 Wiley Periodicals, Inc.